Characterisation and substitution kinetics of cobalt(III) - N-(2-carboxyethyl)iminodiacetato complexes - Potgieter, Johannes Hendrik Wium (University of the Free State, 2004)
The synthesis and reactions of Co(III) complexes with tripod-type ligands such as N-(2- carboxyethyl)iminodiacetic acid (apda) have a widespread interest, mainly because of the fact that these complexes can be used as biological model complexes and because apda labilises usually inert metal centres. The first Co(III)-apda complex was prepared by Tsuchiya and co-workers (1969:1886), this complex was later conclusively characterised by Gladkikh and co-workers (1997:1346) as [Co(apda)(H2O)2] by means of X-ray crystallography. Since then very few metal complexes containing apda as ligand are cited and little or no kinetic studies have been published on these types of complexes. The question regarding the identity of the different Co(III)-apda species in solution at different pH levels has been accounted for in this study (refer to Scheme 1). Scheme in PDF full text. N-(2-carboxyethyl)iminodiacetic acid (apda) was synthesised according to a method obtained from Niclós Gutiérrez (University of Granada). The synthesis of apda was confirmed by means of IR and 1H NMR spectrometry [Co(apda)(H2O)2] was prepared similar to the method described by Tsuchiya and coworkers (1969:1886). The synthesis of [Co(apda)(H2O)2] was confirmed by means of IR, UV/VIS and 1H NMR spectrometry. The IR stretching frequencies obtained for [Co(apda)(H2O)2] are indicative of COO- groups coordinated to a metal centre such as Co(III). The 1H NMR spectrum also indicated that apda acts as a tetradentate ligand with the longer propionato ring in the G (out-of-plane) position. An acid base equilibrium is observed when the pH of a [Co(apda)(H2O)2] solution is increased. It was concluded that the newly formed species is [Co(apda)(H2O)(OH)]- which is unstable at pH > 7, possibly due to dimer formation. The pKa was spectrophotometrically determined as 6.23(2). The substitution reactions between [Co(apda)(H2O)2]/[Co(apda)(H2O)(OH)]- and NCSions have been investigated. At pH = 2.00 NCS- ions substitute the aqua ligands in a stepwise fashion. The substitution of the first aqua ligand of [Co(apda)(H2O)2] (k1 = 14(1) x 10-3 M-1 s-1 at 25.0 °C) at low pH is about 125 times faster than the rate of substitution of the second aqua ligand (k3 = 1.2(6) x 10-4 M-1 s-1 at 25.0 °C). The [Co(apda)(H2O)(OH)]- complex reacts about 70 times faster at 25.0 °C with NCS- than the [Co(apda)(H2O)2] complex with NCS- (k2 = 0.986(8) M-1 s-1 vs. 14(1) x 10-3 M-1 s-1 for k1 at 25.0 °C). This clearly indicates that the hydroxo ligand labilises the cis-aqua bond so that an increase in rate is observed. Hydroxide is not substituted by NCS- ions at higher pH so that only one reaction is observed spectrophotometrically. The synthesis and characterisation of a Co(III)-apda complex with apda acting as a tridentate ligand were also undertaken. This complex was characterised by means of IR spectroscopy and X-ray crystallography as [Co(H2O)6][Co(Hapda)2]2Hּ2O. This complex crystallises in the triclinic space group P ī (R = 0.0228). The two anionic units, [Co(III)(Hapda)2]-, differ in terms of bond lengths and angles as well as strain experienced by the glycinato rings of the apda ligand. This is the first Co(III)-apda complex with two tridentate apda ligands bonded to the same cobalt centre. This complex was also synthesised in the absence of competing ligands. The strain experienced by the glycinato rings of the coordinated apda decreases in the order G > R for all the complexes studied. The R rings in all the complexes are almost perfectly planar in all cases, whilst the G rings are non-planar. The synthesis and characterisation of Na[Co(Hapda)2]xּH2O were also undertaken. This complex was characterised by means of IR, UV/VIS and 1H NMR spectrometry. Two acid base equilibria are observed when the pH of a Na[Co(Hapda)2]xּH2O solution is decreased. It was concluded that the species present at pH 5.5 is [Co(apda)2]3- and that the [Co(Hapda)(apda)]2- and [Co(Hapda)2]- complexes form upon the addition of H+ to this solution. The two acid dissociation constants, pKa1’ and pKa2’, were spectrophotometrically determined as 2.6(1) and 2.8(1), respectively. The various Co(III)-apda complexes that were isolated and characterised can successfully be used as biological model complexes in future studies. These complexes could for example be used to simulate the bonding of metal ion to functional groups of wool fibre or might have uses as models in pharmacology.

Die sintese en reaksies van Co(III) komplekse met driepoot-tipe ligande soos N-(2- karboksieetiel)iminodiasynsuur (apda) lok wye belangstelling omdat hierdie komplekse as biologiese modelkomplekse gebruik kan word en omdat die apda ligand metaalsentra wat gewoonlik inert is, labiliseer. Die eerste Co(III)-apda kompleks is berei deur Tsuchiya en medewerkers (1969:1886), hierdie kompleks is later gekarakteriseer deur Gladkikh en medewerkers (1997:1346) as [Co(apda)(H2O)2] deur middel van X-straal kristalstruktuurbepaling. Sedertdien is weinig ander komplekse met apda as ligand gekarakteriseer en is byna geen kinetiese studies in verband met hierdie tipe komplekse gepubliseer nie. Die vraag rondom die indentiteit van die verskillende Co(III)-apda spesies in oplossing (sien Skema 1) by verskillende pH’s is grootliks in hierdie studie beantwoord. Skema in PDF volteks. N-(2-karboksieetiel)iminodiasynsuur (apda) is gesintetiseer volgens ‘n metode wat van Niclós Gutiérrez (Universiteit van Granada) verkry is. Die sintese van apda is bevestig met behulp van IR en 1H KMR spektrometrie. [Co(apda)(H2O)2] is gesintetiseer volgens die metode wat beskryf is deur Tsuchiya en medewerkers (1969:1886). Die sintese van [Co(apda)(H2O)2] is bevestig met behulp van IR, UV/VIS en 1H KMR spektrometrie. Die IR strekkingsfrekwensies van die [Co(apda)(H2O)2] kompleks dui op COO- groepe wat gekoördineerd is aan metale soos Co(III). Die 1H KMR spektrum dui ook aan dat apda as ‘n tetradentate ligand in hierdie kompleks optree met die langer proprionato ring wat die G (uit-die-vlak) posisie beklee. ‘n Suur-basis ewewig is waargeneem toe die pH van ‘n [Co(apda)(H2O)2] oplossing verhoog is. Daar is tot die gevolgtrekking gekom dat die nuwe spesie wat vorm die [Co(apda)(H2O)(OH)]- spesie is wat onstabiel is by pH > 7, moontlik as gevolg van dimeer vorming. Die pKa is spektrofotometries as 6.23(2) bepaal. Die substitusiereaksies tussen [Co(apda)(H2O)2]/[Co(apda)(H2O)(OH)]- en NCS- ione is ook ondersoek. NCS- substitueer die akwaligande stapsgewys by pH = 2.00. Die substitusie van die eerste akwa ligand van [Co(apda)(H2O)2] (k1 = 14(1) x 10-3 M-1 s-1 by 25.0 °C) by lae pH is ongeveer 125 keer vinniger as die tempo van die tweede akwasubstitusie (k3 = 1.2(6) x 10-4 M-1 s-1 by 25.0 °C). Die [Co(apda)(H2O)(OH)]- kompleks reageer ongeveer 70 keer vinniger by 25.0 °C met NCS- as die [Co(apda)(H2O)2] kompleks met NCS- (k2 = 0.986(8) M-1 s-1 vs. 14(1) x 10-3 M-1 s-1 vir k1 by 25.0 °C). Hierdie resultate toon duidelik dat die hidroksoligand die cis-akwa binding sodanig labiliseer dat ‘n toename in tempo waargeneem word. Verder toon dit aan dat die hidroksie ligande nie deur NCS- ione by hoër pH gesubstitueer word nie aangesien slegs een reaksie by hierdie pH waargeneem word. Die sintese en karakterisering van ‘n Co(III)-apda kompleks, waar apda as tridentate ligand optree, is ook onderneem. Hierdie kompleks is gekarakteriseer met behulp van IR spektroskopie en X-straal kristalstruktuurbepaling as [Co(H2O)6][Co(Hapda)2]2Hּ2O. Hierdie kompleks kristalliseer in die trikliniese ruimtegroep P ī (R = 0.0228). Die twee anioniese eenhede, [Co(III)(Hapda)2]-, verskil in terme van bindingsafstande en hoeke sowel as die verwringing wat deur die glisinato ringe van die apda ligand ondervind word. Hierdie is die eerste Co(III)-apda kompleks met twee tridentaat-gekoördineerde adpa ligande wat aan dieselfde metal sentra bind. Hierdie kompleks is ook in die afwesigheid van kompeterende ligande gesintetiseer. Die verwringing van die glisinato ringe van gekoordineerde apda neem af in die volgorde G > R vir al die komplekse wat ondersoek is. Die R ringe is amper ten volle planêr vir al die gevalle, terwyl die G ringe almal nie-planêr is. Die sintese en karakterisering van Na[Co(Hapda)2]xּH2O is ook onderneem. Hierdie kompleks is gekarakteriseer met behulp van IR, UV/VIS en 1H NMR spektrometrie. Twee suur-basis ewewigte is waargeneem tydens die verlaging van die pH van ‘n Na[Co(Hapda)2]xּH2O oplossing. Die gevolgtrekking is dat die spesie wat teenwoordig is by ‘n pH van 5.5 die [Co(apda)2]3- kompleks is en dat die [Co(Hapda)(apda)]2- en [Co(Hapda)2]- komplekse vorm met die addisie van H+ by hierdie oplossing. Die twee suur-basis ewewig konstantes, pKa1’ and pKa2’, is spektrofotometries as 2.6(1) en 2.8(1) bepaal. Die verskeie Co(III)-apda komplekse wat geïsoleer en gekarakteriseer is in hierdie studie kan suksesvol as biologiese modelkomplekse gebruik word in toekomstige studies. Hierdie komplekse kan byvoorbeeld gebruik word om die binding van ‘n metaal aan ‘n funksionele groep van wol na te boots of kan gebruik word as modelkomplekse in farmakologie.
Dissertation (M.Sc. (Chemistry))--University of the Free State, 2004
Keywords: Cobalt(III); Ionisation constants; Substitution reactions; X-ray crystallography; N-(2-carboxyethyl)iminodiacetic acid; Cobalt compounds